Turgenjev in slovenska varianta "poetičnega realizma" - Barbarič, Štefan (Slavistična revija, 1983)
In the first part of his study, the author takes stock of the first occurances of the term Realism in Slovenian literature; in the second part, he describes Celestin's and Kersnik's dependence on Turgenev in founding their realist doctrine.
Keywords: Celestin, Fran; Kersnik, Janko; literarna zgodovina; literarni teoretiki; literarni vplivi; poetični realizem; realistična doktrina; slovenska književnost